Nomination rules and the calculus of mobilization: Theory and evidence from Mexico. (April 2023) - Ascencio, Sergio J.
Abstract: Does party organization shape candidates' electoral mobilization efforts? I develop a novel theoretical account linking candidate selection rules to electoral mobilization. Nomination rules that require aspiring candidates to compete in electoral races, such as primary elections, create incentives for them to make considerable investments in order to win the party's nomination. Using a decision-theoretic model, I show how these initial investments at the nomination stage shape the candidates' mobilization expenditures in the general election. The main theoretical result establishes that primaries increase candidates' mobilization efforts only when the general election is not expected to be competitive; when a close race is expected, candidates mobilize at the same rates regardless of how they were nominated. Analysis of an original dataset on candidate selection and electoral mobilization in Mexico provides strong support for the theory.